Taxation of non-resident digital companies providing services in South Africa - Shumba, Marilyn Tatenda (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
The role played by electronic commerce has increased in recent years and continues to increase. Due to this increase in the buying and selling of digital goods and services, revenue authorities have had to recognise that the existing taxation laws do not adequately tax the digital economy. The goal of this research was to establish how South Africa could amend its fiscal legislation in order to adequately tax the digital economy. The Organisation for Economic Co-Operation and Development (OECD) has been the leader in addressing the challenges posed by the digital economy. The thesis therefore focused on the recommendations by the OECD on how to tax the digital economy and relevant recommendations for South were adopted in this thesis, based on the work of the OECD. The main focus of these recommendations was on implementing the International VAT/GST Guidelines that were drafted by the OECD. The thesis also focused on the progress made by New Zealand with regard to taxing of the digital economy. New Zealand has a similar taxation system to South Africa so that the progress made there was relevant in the South African context. Recommendations were also made, based on the proposals by the New Zealand revenue authority that South Africa could adopt in taxing the digital economy. The main focus of these recommendations was lowering the Value-Added Tax (VAT) registration threshold for non-resident suppliers of electronic services and enacting legislation to provide for registration of an electronic marketplace for VAT purposes, instead of an individual supplier.
Keywords: Electronic commerce Taxation Law and legislation -- South Africa; Value-added tax -- South Africa; Organisation for Economic Co-operation and Development; Taxation Law and legislation -- South Africa; Business enterprises, Foreign Taxation Law and legislation -- South Africa